A 39000 Mr Immunodominant Protein of Fowlpox Virus Contains Multiple Copies of a 12 Amino Acid Repeat Sequence - Binns, Matthew; Mason, Christine; Boursnell, Michael (Journal of General Virology, 1990)
The nucleotide sequence of an unusual fowlpox virus gene which maps immediately upstream from the fowlpox virus 4b gene has been determined. The 34000 M r protein predicted to be encoded by the gene contains 11 copies of a 12 amino acid serine-rich repeat sequence. The seven amino-terminal copies of the repeat sequence are perfectly conserved but variation exists in the four carboxy-terminal copies. Three peptides were synthesized which contained either one copy of the repeat sequence, two copies of the repeat sequence or a hydrophilic amino-terminal region of the protein. All three peptides when injected with adjuvant into rabbits gave rise to antibodies which reacted strongly on Western blots of purified fowlpox virus proteins with a 39000 M r protein. When directly compared in Western blots the antipeptide sera were shown to recognize a protein comigrating with one of the two immunodominant proteins recognized by chicken anti-fowlpox virus sera taken 2 weeks postinfection. The virion protein is removed by treatment with sodium deoxycholate suggesting that it is located at or near the surface of the virus.